FAKTOR LINGKUNGAN SOSIAL, LINGKUNGAN FISIK, DAN PENGENDALIAN PROGRAM DBD TERHADAP KEJADIAN DEMAM BERDARAH DENGUE (DBD) - Murwanto, Bambang; Trigunarso, Sri Indra; Purwono, Purwono (Jurnal Kesehatan, 2019)
Dengue Bedarah Fever (DHF) one of the problem of the disease in Indonesia and including 30 countries in the world endemic for dengue disease, even though be second place disease in 2015 with a Case Fatality Rate (CFR) of 0.95%. Besides in Lampung in the last three years (2014-2016) tendency for Incidence Rate (IR) is increasing. In South Lampung Regency as the gateway to Sumatra Island in 2017 the Incidence Rate (IR) averaged 20.78% and one of the highest Incidence Rate (IR) reached 70.59% in the Hajimena Health Center Working Area, Natar District. The purpose of this study was to find out the relationship between the factors of the Social Environment, Physical Environment, and the Factors of Controlling the DHF Control Program, and factors were the most dominant relationships. The research method is quantitative with the Cross-Sectional approach, with the study population in the Hajimena Community Health Center Working Area, Natar District, which includes three villages namely Hajimena village, Sidosari village, and the Pemanggilan village. Primary data is taken using questionnaires and checklists, and secondary data is sourced from Puskesmas and Kecamatan. Processing data using data processing software by analyzing using univariate, and bivariate methods. The results of this study show that there is a meaningful relationship are the mobility of the population with the incidence of disease. To eradicate dengue in the Natar sub-district, especially the Hajimena Public Health Center area which is an endemic area, it also requires comprehensive and integrated activities, namely PSN-DBD with periodic larvae checks by cadres of the Larvas Monitoring.